Pengemasan dan Pemasaran Digital Produk UMKM Desa Empat Balai-Kuok, Kampar - Eni Yulinda; Togi Ulla Dharmawan; Ribka Septiani Panjaitan; Futri Aryaningsih; Stefanus Yesaya; M.Hafiz Trimayuda; Michael Geremia Siagian; Syafanissa Dewita Ayura; Nahya Azzahra; Sisilia Yunita; Zaharatul Aini (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2023)
In the context of Empat Balai Kuok village, the Micro, Small and Medium Enterprises (MSME) sector has diverse product types with better development potential. However, the survey results indicate that several MSMEs still face challenges in understanding and building brand identity (branding) for their products. The Kukerta Integration group work program aims to increase the empowerment of local MSMEs by focusing on improving product quality, which will enable wider marketing expansion. The implementation of the work program by the Kukerta Integration Group has involved structured task allocation. One of the roles carried out is the event coordinator for the socialization of marketing strategies and administrative aspects of business licensing. Apart from that, this role also involves conveying knowledge about the assistance resources provided by the government to support the development of MSMEs. The KKN team has also carried out an in-depth analysis of the level of knowledge of the Empat Balai village community regarding marketing, where significant deficiencies were found, such as the absence of logos, labels with expiration date information, and product composition. These aspects should be attractive factors for potential buyers